Protocol for improvement and implementation based on mobile pre-hospital care feedback focused on first rescuers (Research, Society and Development, 2025)
According to Brazilian legislation, rescuers must undergo training programs. In this sense, it may be advantageous to develop training and continuing education based on each professional's own experiences, in order to optimize and improve the services provided to drivers and pedestrians during incidents. One of these methods is called feedback. Thus, the main purpose of this work was to develop a learning and improvement protocol based on rescuers' own experiences, with the aim of training and optimizing the work of these professionals. The systematized method presented in this work consists of two phases, the first of which is composed of the occurrence and the second of the post-occurrence (5 stages), in which rescuers will undergo a process of improvement and learning, based on their own experiences and experiences. In the first stage of the second phase, the team will receive a questionnaire with a maximum of 6 questions. For the elaboration of the questions, the Ishikawa diagram, also known as Cause and Effect Diagram or Fishbone diagram, which was adapted to the reality of rescuers, will be followed. It is concluded that the systematized method presented by the present work can effectively contribute to the process of improvement and learning of rescuers. Since it uses its own experiences and experiences, it also contextualizes it for a more dynamic learning.